2022
DOI: 10.12688/f1000research.53823.2
|View full text |Cite
|
Sign up to set email alerts
|

Obesity correlated to a higher risk of acquiring periodontitis: a cross-sectional study

Abstract: Background: The present study aimed to investigate the correlation between obesity and periodontitis, among other risk factors for periodontitis.   Methods:  In total, 262 Indonesian male and female subjects were analysed for body mass index (BMI), oral hygiene, plaque index, and clinically evaluated periodontitis. Statistical analysis was performed using Spearman tests and Pearson chi-square tests to estimate the correlation between BMI and periodontitis. Multivariate binary logistic analysis was conducted be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A few studies reported other periodontal parameters such as gingival inflammation [36,37], BOP [42], and tooth loss [41,[46][47][48]. Tooth loss showed no association with increased BMI in a study [41].…”
Section: Human Studiesmentioning
confidence: 85%
See 4 more Smart Citations
“…A few studies reported other periodontal parameters such as gingival inflammation [36,37], BOP [42], and tooth loss [41,[46][47][48]. Tooth loss showed no association with increased BMI in a study [41].…”
Section: Human Studiesmentioning
confidence: 85%
“…This review included 15 observational studies from Brazil, Iran, Jordan, Egypt, India, and Turkey (Table 1). Among these, there were nine cross-sectional studies [34][35][36][37][38][39][40][41][42], two casecontrol [43,44], and four cohort studies [45][46][47][48]. The total study subjects from these studies were 6603 (males = 3432; females = 3171).…”
Section: Human Studiesmentioning
confidence: 99%
See 3 more Smart Citations